Analysis of Surface Texture of Asphalt Mixture with Sand Circle Method - Sulandari, Eti; Lestyowati, Yoke; Widodo, Slamet; Felderika, Felderika; Sutarno, Sutarno (Fakultas Teknik Universitas Tanjungpura, 2024)
A road is usually defined as an infrastructure connecting a zone to other zones. As service and safety are essential for vehicle users, any conditions related to the pavement, including surface texture, are considered. The importance of this matter is that many researchers or practitioners are concerned with the quality of asphalt mixtures, whether structural or functional, which affect the safety and security of road users, mainly related to the texture of the pavement surface. This research aims to determine the texture depth (MTD, Mean Texture Depth). The research method used is the circle sand method, which is tested using the Sand Patch tool. The asphalt mixture type uses AC-WC with a composition of 39% coarse aggregate, 54.5% fine aggregate, and 6.5% filler. Optimum Asphalt Content of 6.28% and Density of 2.28 were obtained, and texture depth of 0.549 mm was more significant than 0.45 mm (Bina Marga 2010 revision 3). The conclusion is based on the design composition of the aggregate mix in the AC-WC asphalt mixture, which has a safe texture.